Impact of straw return on greenhouse gas emissions from maize fields in China: meta-analysis - Sun, Qi; Gu, Xue-jia; Wang, Yu-feng; Gao, Hong-sheng; Wang, Xiao-jun; Chen, Xue-li; Sun, Si-miao (Frontiers in Plant Science, 2025)
IntroductionAn increase in the amount of greenhouse gases (GHGs) in the atmosphere causes global warming, and >14% of all GHG emissions come from agricultural activities. The three primary atmospheric GHGs are CO2, CH4, and N2O; therefore, regulating GHG emissions from agroecosystems is important for global climate management. Straw return is an environmentally friendly agricultural practice that positively affects crop production and soil fertility. However, its effects on long-term GHG emissions remain controversial.MethodsTo examine the impact of straw return on GHG emissions from Chinese maize fields, 281 data pairs from 45 publications were assessed using a data meta-analysis.ResultsThe findings demonstrated substantial increases in CO2 and N2O emissions of 140 and 40%, respectively. Methane emissions increased by 3% after straw return, and the maximum effect value of CO2 emissions was 2.66 at nitrogen rates<150 kg/hm2. The effect value of CH4 emissions increased with an decrease in soil organic content, and the effect value of CH4 emissions changed from negative to positive at concentrations >6 g/kg. With a nitrogen rate increase, N2O emission effects under straw return initially increased and then decreased. N2O emissions increased significantly when nitrogen rates were<250 kg/hm2. The results of a random forest model showed that the most important factor affecting CO2 and N2O emissions from corn fields under straw return was the amount of nitrogen applied, and the most important factor affecting CH4 emissions from corn fields under straw return was soil organic carbon content.DiscussionThis shows that a suitable straw return can achieve the mutually beneficial goal of guaranteeing food security and minimizing adverse effects on the environment.